The last temptation - Gaiman, Neil; Zulli, Michael; Klein, Todd (Milwaukie, Oregon Dark Horse Books, 2005)
This graphic novel, based on a story by Neil Gaiman and Alice Cooper, introduces Steven, who is afraid of just about everything until he meets the mysterious Showman and his Theatre of the Real. Steven watches the show on a dare, but then he learns what it is to be truly afraid. Illustrations.
Keywords: Fear -- Comic books, strips, etc; Temptation -- Comic books, strips, etc